Sfrp5 mediates glucose-induced proliferation in rat pancreatic β-cells. Issue 2 (May 2016) - Guan, Binbin; Li, Wenyi; Li, Fengying; Xie, Yun; Ni, Qicheng; Gu, Yanyun; Li, Xiaoying; Wang, Qidi; Zhang, Hongli; Ning, Guang
Abstract : The cellular and molecular mechanisms of glucose-stimulated β-cell proliferation are poorly understood. Recently, secreted frizzled-related protein 5 (encoded by Sfrp5 ; a Wnt signaling inhibitor) has been demonstrated to be involved in β-cell proliferation in obesity. A previous study demonstrated that glucose enhanced Wnt signaling to promote cell proliferation. We hypothesized that inhibition of SFRP5 contributes to glucose-stimulated β-cell proliferation. In this study, we found that the Sfrp5 level was significantly reduced in high glucose-treated INS-1 cells, primary rat β-cells, and islets isolated from glucose-infused rats. Overexpression of SFRP5 diminished glucose-stimulated proliferation in both INS-1 cells and primary β-cells, with a concomitant inhibition of the Wnt signaling pathway and decreased cyclin D2 expression. In addition, we showed that glucose-induced Sfrp5 suppression was modulated by the PI3K/AKT pathway. Therefore, we conclude that glucose inhibits Sfrp5 expression via the PI3K/AKT pathway and hence promotes rat pancreatic β-cell proliferation.